Diskusi Fiqh Dalam Karya Al-Tibb Al-Nabawi Karangan Ibn Qayyim Al-Jauziyyah: Suatu Tinjauan - Muhammad Akmalludin Mohd Hamdan; Syed Mohamad Zainudin Bichk Koyak; Ahmad Salahuddin M Azizan (Fakulti Pengajian Quran dan Sunnah, 2025)
E-Proceeding The9th International Conference on Nabawi Heritage(SWAN 2024) Theme: Prophetic Legacy in Development of Civil Society in the Era of Artificial Intelligence (AI) 6-7 November 2024